PUBLIC BUILDING DAMAGE ANALYSIS AND MAINTENANCE COSTS ESTIMATION - Andeska, Yurenta; Bahaswan, Rizal (E-Jurnal SPIRIT PRO PATRIA, 2025)
Based on the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 related to the Guidelines for Maintenance and Maintenance of Buildings, a building is a physical form of construction work that is united with its position, part or all of it is above and/or in the soil and/or water, which is useful for human space to carry out activities either for space or residence, religious activities, business activities, social, cultural activities, or certain activities. (Hening, 2021). In line with the service life of a building, whether it is a new building or a long time old, it will have an impact on the use of the building which will cause damage, meaning that it is needed as early as possible related to the analysis of building damages that will have an impact on the less than optimal function of the building's performance so that it requires optimal maintenance.